Preliminary Effects of a Structured Group Sports Games Program on Psychological Resilience Among Primary School Students - Qiuyi, Tan; Kambhu Na Ayudhaya, Paradee; Aeumtassana, Thammachote (วารสารศิลปการจัดการ, 2026)
Psychological resilience is important for children’s mental health, school adaptation, and positive development, especially during the transition period of late primary school. Globally, approximately one in seven adolescents aged 10–19 experiences a mental health condition, and schools are important settings for socio-emotional learning and psychological well-being (World Health Organization, 2025). This study examined the preliminary effects of a structured group sports games program on psychological resilience among Grade 6 primary school students. A small-scale pretest–posttest control-group school-based intervention design was used. After school permission and consent procedures, 300 Grade 6 students from Cheng Shuren Primary School of Chongqing University completed screening. The 30 students with the lowest total psychological resilience scores were selected and randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group participated in a 5-week program consisting of 10 sessions, twice per week, approximately 40 minutes per session. The control group continued usual school activities and regular physical education classes but did not receive the structured program. Psychological resilience was measured using a 20-item scale adapted with reference to Hu and Gan, covering goal focus, interpersonal support, emotional regulation, and positive cognition. Reliability was acceptable to good, with an overall Cronbach’s alpha of .91. Descriptive statistics, t-tests, effect sizes, 95% confidence intervals, and SPSS mixed-design ANOVA were used. The experimental group showed higher post-test mean scores in overall psychological resilience and all four dimensions; post-test group differences were statistically significant for total resilience, goal focus, and interpersonal support. Mixed-design ANOVA further indicated significant group × time effects for total resilience and all four dimensions. However, because the study used a small sample from one school and a short intervention period, the findings should be interpreted cautiously and verified in larger studies.